Emphasizing Electro-Thermal Dynamics for Design, Modeling, and Control of Microgrids - Asmaou S. Ouedraogo; Donald J. Docimo (IEEE Access)
This article studies the design, modeling, and control of microgrid systems with the inclusion of internal electro-thermal dynamics. Microgrids play a vital role in integrating renewable energy and enabling distributed energy systems. However, their complexity arising from diverse and dynamic components necessitates advanced control strategies. While existing works often utilize model-based controllers, the focus is primarily on electrical dynamics, with limited attention to the thermal behavior of components. The intricate interplay between electrical and thermal power terms heavily impacts component behavior, exemplified by the dependency of photovoltaic (PV) module electricity production on temperature. This article addresses the limited studies on electro-thermal microgrid dynamics through three contributions. First, a candidate microgrid design is developed to utilize electro-thermal knowledge, incorporating active cooling for PVs. Second, a graph-based modeling methodology is expanded to represent microgrid component- and system-level dynamics. Third, a hierarchical control framework is developed to define controllers for microgrids using the graphical model. Controllers produced from the framework enable management of electro-thermal behavior while adhering to battery charge limits. Case studies utilizing realistic environmental data are explored to evaluate the performance of the proposed system. Results indicate design and model-based control that integrate electro-thermal dynamics provide improvements to energy generation and performance even under nonideal conditions.